Sejarah Sosial-Politik Arab: Dari Hegemoni Romawi-Persia Hingga Kebangkitan Arab Islam - Ahmad Agis Mubarok (IAIN Palangka Raya, 2020)
This article focused on studying the socio-political history of Arabia from Roman-Persian hegemony to the rise of Islamic Arabs. The study was motivated by the historical disintegration developed among academics. History was understood in a variety of ways without clear accentuation of the developing storyline. Previous studies did not explain in detail about the social-political history of Arabia. In this way, it was necessary to re-emerge Arab social-political history with different perspectives, methods and systematic discussion, so that it was interesting to read. In this article, the author used the method of biographical and bibliographic history, a method that analyzed the nature, character, and influence of a civilization to then, it was interpretd and generalized the historical facts that surround it. The data sources were obtained from books on Arab and Islamic history, such as the book History of the Arabs by Philip K. Hitti, Ali Jawwad's Arabic History before Islam, Sirah Nabawiyah by al-Buthy, History of the Islamic Society by Hamka. The results indicated that the Arabs had a hard character, independent, solidarity, and royality towards their groups. Arab social-political atmosphere were colored by political intrigue over the struggle for influence between the three major powers of the world at that time, namely Roman, Persian, and South Arabian kingdoms under the rule of the Himyar dynasty. The rise of Arabia was marked by the birth of Islam in Hijaz. Arabic when Islam was born had great influence and civilization in the economic, social, political, cultural and scientific fields.Keyword : Socio-Political, Roman-Persian, Arab Nation